Keadilan Restoratif dalam Dinamika Pembaruan Hukum Pidana Indonesia - Hasna Afifah (Syntax Corporation Indonesia, 2024)
The purpose of this study is to assess the effectiveness of the implementation of restorative justice in handling certain criminal cases in Indonesia. The type of research used is descriptive. Which means that this research will be discussed in the form of a presentation that is elaborated in words carefully and thoroughly. In this case, the presentation of the concept of restorative justice as a means of resolving non-litigation cases (outside the court) and its relevance to the dynamics of criminal law reform in Indonesia. The approach method in this study is a normative juridical approach method. As a result, criminal law reform must be formulated with a policy-oriented approach, as well as an approach oriented to the values that live in society. Restorative justice as one of the alternative case resolution in the criminal justice system that focuses on restoring the original situation by involving victims, perpetrators and the community is one of the efforts in criminal law reform that is oriented not only to retaliation.